Is the Ketogenic Diet Effective and Safe in Children with Intractable Epilepsy? A Systematic Review - Razan, Rafi Alfian; Hanindita, Meta Herdiana; Ramadhani, Ayuning Tetirah; Putri, Melvanda Gisela; Harum, Nabila Annisa; Nurrosyida, Kartika (The Indonesian Society of Pediatric Gastroenterology, Hepatology, and Nutrition, 2024)
Background: The ketogenic diet (KD) has long been prescribed to children with recurrent epilepsy due to its minimal neurotoxic effects. The side effects caused this diet to be abandoned. New diets are emerging as options such as modified Atkins diet (MAD), low glycemic index therapy (LGIT) and medium-chain triglyceride (MCT). This study compared the safety and effectiveness of the KD and these new methods. Method: Systematic review was conducted by searching databases such as PubMed, ScienceDirect, SpringerOpen, Cochrane, Proquest and Scopus based on the Preferred Reporting Items for Systematic Reviews and Meta Analyses (PRISMA) guidelines. Result: : A total of 439 pediatric patients aged 0 - 18 years who were intervened with a ketogenic diet compared with other dietary options. A total of five studies reported a higher mean reduction in seizure incidence >90% in children who were intervened with a ketogenic diet compared to other diets, one of which reported KD > MAD (53.3% KD vs. 26.6% MAD). Conclusion: Although KD remains effective, MAD, LGIT, MCT and Polyunsaturated Fatty Acids KD (PUFAKD) diets provide comparable benefits with potential for better adherence. The classic KD group showed a higher morbidity rate; however, it demonstrated significant effectiveness in lowering the incidence of recurrent seizures in children.